INOVASI PRODUK RAMAH LINGKUNGAN : PELATIHAN DAUR ULANG LIMBAH PAKAIAN BEKAS MENJADI PERABOT RUMAH TANGGA UNTUK MENDUKUNG BISNIS KREATIF - Soviyanti, Efrita; Kamilah, Faizah; Khairani, Zulia (Komunitas Manajemen Kompetitif, 2025)
This Community Service Activity aims to provide knowledge about the use of used and used clothes at home into various products that have economic value, in addition to providing training in making household equipment mat products from used clothes. The method of this community service activity uses lecture methods, questions and answers and training with product making tutorials. The lecture method is used to convey general knowledge about the impact of used clothes which can also become waste that decomposes over a long period of time. In addition, the lecture method also conveys various products that can be used as ideas for making other products. The question and answer method is used to complete things that have not been accommodated by the lecture method. Training method with direct tutorials on making household furniture mat products from used clothes. This training involves lecturers from the Accounting and Management Department who work together with the Dasawisma mothers' group in Meranti Pandak Village as target subjects. Keywords: inovasi produk, eco friendly, entrepreneurship,baju bekas